Teleworking as a mitigator of the economic impacts of the CO VID-19 pandemic.The case of Argentina (2021)
We estimate the role of teleworking as a mitigator of the impact of the COVID-19 pandemic shock on the Argentine labor market. To that aim, we analyze the link between occupational-level teleworking potential scores, estimated from three different surveys (O*NET, PIAAC, and STEP) and labor market outcomes at the individual level, exploiting the rotating panel structure of the Argentine national household survey. We find that during the peak of the pandemic-related restrictions, the potential for teleworking was positively correlated with the probability of being active and employed. These effects are concentrated in the subsample of “non-essential” workers. In contrast, we find no systematic effects of teleworking potential on employment transitions prior to the pandemic, a reassuring result consistent with our identification strategy.